Design Management System Exams Test in STMIK Jakarta STI & K - Abrar Nasbey (Jurnal Sistem Informasi, 2005)
Systems courses in STMIK Jakarta STI & K consists of 2 semesters in year. Ditiap-each semester the students will face the test twice, the Central Examination Semester (UTS), Final Examination Semester (UAS), and the Main Examination (Exam Quality Control). To assist the Faculty in managing exam questions required a simple program used by the lecturer, and can be accessed within the STMIK Jakarta STI & K with a system that can be kept confidential so as not to be viewed by students, about the security level of reliability, and problem tracking mechanism in order to assist in the validation problem. In order to facilitate the lecturer, in making the problem, edit, and arrange about ready to be tested can be done indefinitely, could at any time.